Exploring The Rooms with Lykta Creating Immersive Gaming Experiences through Projected Augmented Reality - Michelsen, Jacob (My University, 2014)
The immersive gaming capabilities of projected augmented reality using a prototype system, Lykta, are investigated. To accomplish this a horror game is designed and implemented, drawing design methods from the fields of game design and interaction design. An approach with two design iterations is used, followed by a playtest in which interviews and questionnaires are used to gauge the immersiveness of the experience provided by the game. Throughout the process, improvements are made to the prototype system. The result is a game played in a dark room. The experiences provides the players with the illusion of exploring the game world using just a flashlight, which in reality is a projector projecting out the game. The results from the playtest are compared to several different kinds of immersion, with findings showing that the players had at least to some degree experienced several different kinds of immersion. Future evaluations of a more quantitative and comparative nature are suitable for determining the immersive aspects of projected augmented reality in more detail, but tentative results suggest that a new type of immersion, spatial immersion, might be a relevant addition to other immersion models.
Keywords: Informations- och kommunikationsteknik; Människa-datorinteraktion (interaktionsdesign); Information & Communication Technology; Human Computer Interaction